Similaritas dan Korelasi Tumbuhan Invasif pada Tegakan Eksotik di Kawasan Lindung di Kawasan Lindung PT Musi Hutan Persada, Sumatera Selatan - Huda, Muhammad Komarul; Setiawan, Arum; Oktariansyah, Yadi; Yustian, Indra; Setiawan, Doni; Pragustiandi, Guntur; Pranoto, Aidil Fitra (Journal of Natural Sciences, 2026)
Invasive alien plants pose a major threat to biodiversity, particularly in conservation areas embedded within industrial plantation forest landscapes dominated by exotic species. This study aimed to analyze the composition and dominance of invasive plants, community similarity, and their correlations with Acacia mangium and Eucalyptus pellita stands in the Protected Area of PT Musi Hutan Persada, South Sumatra. Vegetation analysis was conducted using a nested quadrat sampling method across four stand types (control, A. mangium-dominated, E. pellita-dominated, and mixed stands), with 60 purposively selected plots. Data were analyzed using the Important Value Index (INP), Jaccard similarity index, and Spearman correlation. The results identified 20 invasive plant species, with Eleusine indica as the most abundant. A. mangium and E. pellita exhibited the highest INP at the tree stratum. Similarity analysis indicated variation in species composition, with a tendency toward community homogenization in some locations (≥0.80). Correlation analysis revealed that A. mangium was positively associated with Imperata cylindrica and Chromolaena odorata, while E. pellita was associated with Clidemia hirta and Piper aduncum. These findings highlight the ecological role of exotic stands in shaping the distribution patterns of invasive plants.